Analysis of Factors Affecting Employee Productivity (Study on the Employee of PT Arkan Teknik Medan) - Niken Wulandari (CERED Indonesia Institute, 2022)
The purpose of this study is to determine the effect of compensation on work productivity, to determine the effect of the work environment on work productivity and to determine the effect of compensation and work environment on work productivity at PT. Arkan Field Engineering. The sampling technique in this study used saturated sampling. namely the determination of a sample of 48 respondents who are employees of the production department at PT Arkan Teknik Medan. This research method was collected through questionnaires that were processed and analyzed using data analysis and Multiple Regression. Then conducting a data quality test used is a validity test using Corrected Item Total and a reability test using Cronbach Alpha to test the hypothesis in this study. Researchers use the t test, and the F test and conduct a determination test. The results of this study showed that there was a significant positive influence of compensation variables on work productivity variables indicated by counting (4,520) > ttabel (1.68) with a significance value of 0.000< 0.05, and there was a significant positive influence of work environment variables on work productivity variables shown by counting (3.713) > ttabel (1.68) with a significance value of 0.001< 0.05, and for compensation and a positive work environment and significant work productivity of employees at PT Arkan Teknik Medan with a calculated value (109,040) > Ftabel (3.19) with a signification rate of 0.000. Furthermore, the R Square value obtained was 0.829 indicating about 82.9% significant influence of compensation and working environment.